A fixação dos critérios de apuração de haveres na sociedade limitada: uma análise empírica e estatística da jurisprudência - Adoglio, Tatiana Marques (2022)
This present body of work analyzed whether after the enactment of the new Civil Procedure Code of 2015, which introduced an unprecedented and special procedure for the partial dissolution of companies, the São Paulo Judiciary began to set criteria for the determination of assets in the partial dissolution of the company. The analysis was carried out through empirical-quantitative legal methodology, through a new discipline of law: Jurimetrics. First, there was a discussion on the historical evolution of the partial dissolution of companies, in order to demonstrate the problem faced by companies, proven through the results of the former research conducted by Professor Marcelo Guedes Nunes through the judicial decisions of the Courts of Justice of Brazil before the enactment of the new Civil Procedure Code of 2015, concluding with the effective evolution of jurisprudence, albeit timidly